2019
DOI: 10.1186/s40862-019-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different text difficulty levels on Iranian EFL learners’ foreign language Reading motivation and Reading comprehension

Abstract: This study investigated the effects of different text difficulty levels on Iranian EFL learners' foreign language reading motivation and reading comprehension. To fulfil this objective, 40 Iranian participants were selected among 50 students based on the results of Interchange Placement Test (Richards et al, Placement and Evaluation Package Interchange Third Edition/Passages Second Edition with Audio CDs, 2008). The pre-intermediate selected participants were then randomly divided into two equal groups; "i + 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 14 publications
0
12
0
2
Order By: Relevance
“…Perhaps, the proposed research plan would then need to include an additional session during the oral presentations where the participants would need to share new vocabulary they have learned and explain the words as used in the reading contexts. On a different note, a study by Niazifar and Shakibaei (2019) seems to disagree with what Vela (2015) claimed. In contrast to the common perception that easy materials may increase the reading motivation of EFL learners, the findings of the study done by Niazifar and Shakibaei (2019) proved that the more difficult materials increased Iranian EFL learners' motivation towards reading English texts.…”
Section: Findings and Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Perhaps, the proposed research plan would then need to include an additional session during the oral presentations where the participants would need to share new vocabulary they have learned and explain the words as used in the reading contexts. On a different note, a study by Niazifar and Shakibaei (2019) seems to disagree with what Vela (2015) claimed. In contrast to the common perception that easy materials may increase the reading motivation of EFL learners, the findings of the study done by Niazifar and Shakibaei (2019) proved that the more difficult materials increased Iranian EFL learners' motivation towards reading English texts.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…On a different note, a study by Niazifar and Shakibaei (2019) seems to disagree with what Vela (2015) claimed. In contrast to the common perception that easy materials may increase the reading motivation of EFL learners, the findings of the study done by Niazifar and Shakibaei (2019) proved that the more difficult materials increased Iranian EFL learners' motivation towards reading English texts. Though there might be differences in ESL and EFL learning contexts, it seems fair to say that this learning scenario may be similar to ESL learning contexts where the learners are under A2 and B1 of the CEFR level of proficiency.…”
Section: Findings and Discussionmentioning
confidence: 85%
“…Both studies considered language-related variations in texts related to tasks as a predictor, and students' motivation as a dependent variable. Niazifar and Shakibaei (2019) varied the level of language demand to determine how different degrees of lexical and grammatical demands of textual materials affect the reading motivation of n = 40 male students learning English as a second language. Participants were divided into two groups, one of which received text material one level above their current English language level, in terms of syntactical structure and vocabulary, over a tenweek period.…”
Section: General Study Characteristics: Sample Setting and Research D...mentioning
confidence: 99%
“…Both studies did this by examining the effects of language-related variation in text tasks, although the variation occurred in different ways in both studies. While Niazifar and Shakibaei (2019) varied grammar and vocabulary to compare different linguistic demands, Reichelt (2015) varied pronouns and addresses for didactic purposes. Despite these different forms of language-related variation, both studies found significant effects on motivation.…”
Section: Comparison Of the Studiesmentioning
confidence: 99%
“…Pengertian membaca pemahaman oleh Rijk (2017) yaitu proses penggalian dan pembentukan makna secara bersamaan melalui interaksi dan keterlibatan dengan teks. Niazifar (2019) menyatakan bahwa membaca pemahaman adalah kemampuan untuk mengambil informasi. Kita telah mengetahui bahwa pembelajaran di kelas II SD sudah menuntut siswa untuk memahami isi bacaan.…”
unclassified